Allium therinanthum (Amaryllidaceae), a new species from Israel - Brullo, Cristian; Brullo, Salvatore; Fragman-Sapir, Ori; Del Galdo, Gianpietro Giusso; Salmeri, Cristina (Phytotaxa, 2014)
Allium therinanthum, a new species of A. sect. Codonoprasum, is described and illustrated from southern Mt. Hermon (Israel). It is a late-flowering diploid species (2n = 16), growing on calcareous substrates of the mountain belt. It is a narrowly distributed geophyte, showing morphological relationships mainly with A. tardiflorum, a typical autumnal species also occurring in Israel within the pinewoods of Mt. Carmel. The morphology, karyology, leaf anatomy, ecology, conservation status and taxonomical relations are examined for both species. A taxonomic comparison with the most allied late flowering species of the sect. Codonoprasum is provided.